PERAN TENTARA CADANGAN ISRAEL DALAM KONFLIK ISRAEL DAN PALESTINA - Mulyadi, Ahmad; Fitria, Laila Indriyanti; Louhenapessy, Matheis Ferdinand (Moestopo Journal of International Relations (MJIR), 2024)
Israel as a country, always seems to find a way into another new conflict with neighboring states, especially with Palestine. The focus of this article will be about explaining how Israel handles a very important issue within their military, which is the slow declining number of military personnel that they are currently facing due to frequent amount of conflict and how long the duration of said conflict. Duration of war could heavily influence the number of military personnel, and could lead to a serious issue, which could cause the collapse of a country. In 1948, Israel found a solution to this issue, Israel decided to form their own Reserve Duty. This branch in the Israel Defense Force consists of civilians, these civilians then receive basic military trainings with the goal of making them eligible to fight in the conflicts that Israel are facing. Reserve Duty of Israel was so vital in their war crime, that the government decided to continue this program until now. In their latest conflict against Palestine citizen (including children and elderly), Israel called thousands of their reserve duty member to aid in the genocidal act against Palestinian civilians. The method of this research is descriptive qualitative, in which the researcher will gather information about the topic of Israel’s Reserve Duty and then will explain them in detail, with the purpose of giving more knowledge and information about this specific conflict and the role of reserve duty army within it. This research explains how the Israel army force depend on its reserve duty to increase their number of manpower and this helps them to maintain power in a conflict, but there are also issues within the usage of reserve duty, such as mental issues, decrease of manpower in the same time due to death toll that keeps adding up, and also the strategy used by Israel often leads to losing its own military personnel.